Detoxication of social media addiction among adolescents through regulatory intervention - Hasmin, Nor Akhmal; Azizun, Najwa; Amit, Siti Marina; Abd Kadir, Nur Hafidah (Faculty of Administrative Science and Policy Studies, 2023)
Democratic nations are commonly associated with the freedom to access various social media platforms, such as Twitter, Instagram, TikTok, Youtube, Snapchat, and Facebook. Unlimited access to these platforms among adolescents has resulted in serious social media addiction, which directly destroyed the fabric of adolescent society. Social issues, the threat to health and mental well-being, and attitude problems are among the negative impacts of social media addiction. The paper outlines the scenario of social media addiction and the regulatory framework in Malaysia for protecting the life of adolescents from being obliterated by social media. Reference is made to the practices in the People’s Republic of China (China) on regulating access to social media among adolescents. Subsequently, this paper examines whether the imposition of regulations that limit the rights to access social media violates fundamental rights granted to the democratic citizen. This study adopts a doctrinal analysis, where materials are collected and compiled from legislations in Malaysia and China, journal articles, and databases. It is found that regulatory intervention is necessary to ensure access to social media can consciously create a constructive adolescent society rather than destroying it. This study is intended for the policymakers and the public to understand the possibility of imposing a hard law regulating access to social media platforms and preventing social media addiction among adolescents.